Moral Issue: Effect of Individualism and Egoism Millennial When Having High Technical Skill on Working Performance - Hiqmatus Sholichah (Jurnal Manajemen dan Bisnis, 2021)
This study aims to determine the effect of individualism and egoism with high-tech millennial skills on work performance at PT XYZ which is a member of the Triputra Group. The population of the study were all 170 employees of PT XYZ. The sample used in this study were 25 employees as respondents obtained by probability sampling with proportional random sampling method. The data collection method used a questionnaire and multiple linear regression data processing techniques. The results of multiple linear regression analysis show that individualism has a negative and significant effect on employee work performance at PT XYZ and egoism has a negative and significant effect on employee work performance at PT XYZ. From these variables, the most dominant variable affecting the work performance of PT XYZ employees is egoism caused by high technical skills and a lack of interest in sharing knowledge and experiences with fellow workers. It is recommended that PT XYZ implement several system methods and work procedures such as employee rotation, skill equalization, skill and competency mapping. For further researchers, it is recommended to add other variables including work environment, compensation, culture and achievement.